Byzantine Fault Tolerance in Soap Communication Services - Sankaranarayanan, Murugan; Veilumuthu, Ramachandran (Malaysian Journal of Computer Science, 2012)
An innovative SOAP communication model with modified message exchange pattern is proposed to identify and eliminate Byzantine faults in distributed services environment. When a request is made by a client to a Web enabled application, it is usually processed by a set of composite Web services. In a system of several coordinating Web services, there is a possibility that one or more services may behave maliciously by exhibiting Byzantine behaviour and it is a challenging task to identify and eliminate them. In the proposed model, the Lamport’s algorithm is utilized to identify the Byzantine faults in the distributed services environment. The services may behave abnormally and exhibit Byzantine behaviour that will lead to faulty response. The response from all the coordinating distributed services is captured and analyzed to determine the presence of Byzantine faults before dispatching the actual response to the client. To induce faults into the services artificially during execution, around advice aspects are adopted. When the fault identified is legitimate, response without any modification is dispatched to the client; otherwise a revised response is generated. In the presence of traitorous behaviour, the faulty service is handled within the new message receiver named as BFTMessageReceiver which is included in the existing message exchange pattern. The BFTMessageReceiver is extended from the original message receiver used in the SOAP communication framework, and hence, the regular response dispatching capabilities are retained.